Eksplorasi Keanekaragaman Aktinomisetes Tanah Ternate Sebagai Sumber Antibiotik - Nurkanto, Arif; Listyaningsih, Febrianti; Julistiono, Heddy; Agusta, Andria (JURNAL BIOLOGI INDONESIA, 2010)
ABSTRACTExploration of Soil Actinomycetes Diversity from Ternate as Indigenous Antibiotic Sources.Actinomycetes of soil samples from Ternate, North Moluccas were isolated using SDS-YEmethod in humic acid vitamin agar. Ternate has high abundance of Actinomycetes, approximately6.00 â 487 x 104 CFU/ g soil, depends on habitat types. We have selected 60 isolates andconducted antibiotic screening against pathogenic bacteria and fungi using agar diffusionmethod and found both narrow and broad antibiotic spectrum types . Based on 16S rDNAanalysis, all Actinomycetes with antibiotic activities are belong to the genus Streptomyces. .Minimum Inhibitor Concentration (MIC) value was determined by broth microdilution method.It was found that MIC values varied, depended on microbial tested. We found two isolateswith higher antibiotic activity compared to the commercial antibiotics (chloramphenicol,erythromycin for antibacterial and nystatin, kabicidin for antifungal). Cell destruction analysiscaused antibiotic activities was conducted through leak of protein and nuclatic acid.Key words : Actinomycetes, soil, Ternate, antibiotic, cell distruction